Hemp (Cannabis sativa L.) protein concentrates from wet and dry industrial fractionation: Molecular properties, nutritional composition, and anisotropic structuring. (October 2022) - Nasrollahzadeh, Farzaneh; Roman, Laura; Swaraj, V.J.Shiva; Ragavan, K.V.; Vidal, Natalia P.; Dutcher, John R.; Martinez, Mario M.
Abstract: Hemp seeds stand as a rich source of globulins and albumins with all the essential amino acids and a balanced amino acid profile. Nevertheless, the potential of dry- and wet-extracted hemp protein concentrates to create plant-based, fibrous High Moisture Meat Analogues (HMMAs) remains unknown. In this study, five distinct hemp seed protein concentrates (55.9–76.4% protein, d.b.) produced at industrial scale using dry or wet fractionation were investigated and compared for their functionality and protein molecular properties. Furthermore, non-proteinaceous components were also analysed to elaborate on the underlying mechanisms for the structuring behaviour of hemp protein concentrates during wet extrusion. Although dry fractionation resulted in lower protein concentration, hemp proteins retained their native oligomeric state and their albumin fraction, thus showing higher surface hydrophobicity and solubility, and lower gelation concentration than wet-extracted counterparts. Furthermore, hemp samples were richer in bound polyphenols (>1800 mg/100 g), presumably phenolic acids, than the control pea sample (1363 mg/100 g), which resulted in dark colours in wet-extracted samples. Selected HMMA prototypes were developed and investigated for anisotropy, viscoelasticity, and proton NMR relaxometry. Visual and instrumental anisotropy dramatically increased with the use of hemp protein concentrates, from 0.69% using pea, to 0.98% and 1.41% using dry- and wet-fractionated fractionated hemp, respectively. Nonetheless, dry-fractionated hemp HMMA showed the highest proportion of free water in the system ( T 23 proton relaxation time), and an intermediate viscoelasticity between pea and wet-fractionated hemp HMMAs. Interestingly, SDS-PAGE revealed a significant contribution of disulphide bonds on hemp protein aggregation during processing. Graphical abstract: Image 1 Highlights: Wet isolation decreased hemp protein surface hydrophobicity, solubility and lightness. Hemp protein samples resulted in meat analogues with visible fibrous-like structures. Dry-fractionated hemp extrudates had the highest proportion of free water. Hemp extrudates showed up to 200% higher anisotropy than the pea protein counterpart. Disulphide bonds played a key role on hemp protein aggregation during extrusion.